Mendalami Keterkaitan Penghindaran Pajak Dari Pertumbuhan Penjualan, Risiko Perusahaan dan Tata Kelola - Ni Luh Mia Deara Mayuni (Jurnal Manajemen dan Bisnis, 2020)
ABSTRACTThis study examines the relevance of tax avoidance as a dependent variable of sales growth, corporate risk as an independent variable and governance as an intervening variable. Governance variables use three indicators, namely independent commissioners, audit committees, and audit quality. The population used in this study is a company that is included in the Kompas100 list with a total of 100 companies. Data collection is done by means of documentation and observation of the annual report on the company under study. The analysis technique used to analyze data is SEM (Structural Equation Model). The results of this study indicate that sales growth has a negative effect on corporate governance and corporate governance has a negative effect on tax avoidance. Sales growth has a positive effect on tax avoidance and corporate risk has a positive effect on corporate governance and tax avoidance. Sales growth in the company can be used to measure the performance of a company. Sales growth and corporate governance can also be used as determinants of company status. The better corporate governance, it will be able to minimize tax avoidance by the company.